Thin Places : a Pilgrimage Home. - Armbrecht, Ann, 1962- (Columbia University Press, 2008)
Thin Places is an eloquent meditation on what it means to move between cultures and how one might finally come home, a particular paradox in a culture that lacks deep ties to the natural world. During the 1990s, Ann Armbrecht, an American anthropologist, made several trips to northeastern Nepal to research how the Yamphu Rai acquired, farmed, and held onto their land; how they perceived their area's recent designation as a national park and conservation area; and whether-as she believed-they held a wisdom about living on the earth that the industrialized West had forgotten.